VISIT STROKE: non-inferiority of telemedicine-based neurological consultation for post-acute stroke patients: protocol of a prospective observational controlled multi-center study - Herm, Juliane Maria; Erdur, Hebun; Aigner, Annette; Hengelbrock, Johannes; Angermaier, Anselm; Flöel, Agnes; Hille, Annegret; Gorski, Claudia; Kinze, Stephan; Schmehl, Ingo; Hubert, Gordian J.; Wiestler, Hanni; et al. (BMC health services research, 2024)
Background: Telemedicine provides specialized medical expertise in underserved areas where neurological expertise is frequently not available on a daily basis for hospitalized stroke patients. While tele-consultations are well established in acute stroke assessment, the value of telemedicine-based ward-rounds in the subsequent in-patient stroke management is unknown. Methods: Four telemedicine stroke networks in Germany, implemented in eight out of 16 federal states, participate in this prospective observational multi-center study. We plan to enroll 523 patients hospitalized due to acute (suspected or confirmed) stroke or transient ischemic attack. Each recruited patient will receive both a tele-consultation and an on-site consultation at the same day within the first three days after hospital admission. We will test non-inferiority of telemedicine-based assessments in ward-rounds in terms of quality of medical assessment and recommendations for hospitalized stroke patients. The correctness of the medical assessment and recommendation is defined as positive evaluation (binary, correct vs. in-correct) of six out of six predefined quality indicators by at least two out of three blinded independent raters. The non-inferiority margin for the difference in proportions of correct assessments is set to 5%-points. Discussion: If non-inferiority of telemedicine-based ward-rounds compared to on-site ward-rounds by a neurologist were emonstrated, telemedicine-based neurological consultation for post-acute stroke patients may contribute to deliver evidence-based high-quality stroke care more easily in underserved regions.
Gesehen am 03.06.2025